Impacto da umidade do minério de bauxita no transporte marítimo - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The present work demonstrates the importance of carrying out the necessary controls in relation to the temperature of the bauxite ore during its loading in the holds of the ships, so that the maritime transport can occur in a safe way. Exploratory-descriptive field research was used as a technique for this study, where data were collected that made it possible to demonstrate the importance of controlling humidity during the entire process of shipping the bauxite ore in the holds of the ship in order to always maintain the content cargo moisture lower than its transportable moisture limit (TML) - regulatory parameter determined through laboratory test methods recognized by the International Maritime Organization. As a result of this process, it is expected that during maritime transport the cargo will not liquefy, which could cause the ship to sink. It was concluded that it is necessary to understand and follow the regulatory aspects determined by the IMO that establishes in its International Maritime Solid Bulk Cargo Code the International Maritime Solid Bulk Cargoes Code (IMSBC Code) as conditions for carrying out such transport.
Keywords: Umidade; Transporte marítimo; Liquefação; Bauxita; CNPQ:: CIÊNCIAS EXATAS